1986
DOI: 10.1139/m86-124
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of the oral cavity of BALB/c mice

Abstract: To be used as a model in dental research, an animal must fulfil experimental needs and information on the composition and variation of its oral flora must be available. Only limited data are available on the indigenous oral bacterial flora of BALB/c mice. In this work, a total of 671 isolates from different sites (saliva, tongue, teeth, and mucosa) of the oral cavity of BALB/c mice were identified. Only 18 different species were isolated, which indicates the relative simplicity of the flora. The predominant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 21 publications
6
48
0
Order By: Relevance
“…The discrepancies observed between these studies may be due to the different techniques used for the isolation and identification of the bacterial isolates and the statistical methods of evaluation. Our techniques were shown to recover 94-99% of the bacterial species present (Rodrigue et al 1989, Trudel et al 1986) and the appropriateness of the statistical methods that we used has already been discussed by Moore et al 1982Moore et al , 1984 The differences between the oral bacteria of BALB/c mice from the various suppliers could be attributed to: (1) significant differences in transit times and (2) the use of different diets by the suppliers (Taconic Farms: Agway NIH-31, Harlan Sprague Dawley: Teklad LM-485, Jackson Laboratory: Diet 911A (Emory), Hilltop Lab Animals: Prolab RMH-3000, Charles River Canada: Purina 5077). We showed previously that a modification of the sugar, starch or protein content of the diet could alter the proportions of the predominant oral bacterial species in BALB/c mice (Blais and Lavoie 1990).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The discrepancies observed between these studies may be due to the different techniques used for the isolation and identification of the bacterial isolates and the statistical methods of evaluation. Our techniques were shown to recover 94-99% of the bacterial species present (Rodrigue et al 1989, Trudel et al 1986) and the appropriateness of the statistical methods that we used has already been discussed by Moore et al 1982Moore et al , 1984 The differences between the oral bacteria of BALB/c mice from the various suppliers could be attributed to: (1) significant differences in transit times and (2) the use of different diets by the suppliers (Taconic Farms: Agway NIH-31, Harlan Sprague Dawley: Teklad LM-485, Jackson Laboratory: Diet 911A (Emory), Hilltop Lab Animals: Prolab RMH-3000, Charles River Canada: Purina 5077). We showed previously that a modification of the sugar, starch or protein content of the diet could alter the proportions of the predominant oral bacterial species in BALB/c mice (Blais and Lavoie 1990).…”
Section: Discussionmentioning
confidence: 96%
“…The proportion of each oral bacterial species was determined by a colony-immunoblot technique (Rodrigue et al 1989, Rodrigue & Lavoie 1990. Bacterial isolates which did not react with any of our specific antisera prepared against the predominant oral bacterial species recovered from the BALB/c mouse from Charles River Canada (Gadbois et al 1993, Rodrigue et al 1989, Trudel et al 1986 were purified by subculturing twice and identified using API test strips (Staph Ident, 20 Strep, 20E, Rapid CHI (Biomerieux Canada, St. Laurent, Qc) (Gadbois et al 1993). The proportion~of the oral bacterial species were compared using the minimal percentage of similarity and the Lambda of Good (Lacroix' & Lavoie 1987, Moore et al 1982, Moore et al 1984 with the level of significance fixed at …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences between individual immunoreactivities against quantitatively different components of the oral flora do not argue for a dose-dependence in the response to oral indigenous bacteria. It is possible, however, that some bacteria recovered at high frequency at oral sites (e.g., S. aureus) are not true residents of the oral ecosystem, being found predominantly in the saliva (28). It must be stressed, however, that Streptococcus sp., including faecalis, are predominantly recovered from oral surfaces (particularly from the teeth) and are likely to be permanent residents of the murine oral cavity.…”
Section: Discussionmentioning
confidence: 99%